Backbone Cyclization and Dimerization of LL-37-Derived Peptides Enhance Antimicrobial Activity and Proteolytic Stability - Gunasekera, Sunithi; Muhammad, Taj; Strömstedt, Adam A.; Rosengren, K. Johan; Göransson, Ulf (Frontiers in Microbiology, 2020)
Can antimicrobial activity and peptide stability of α-helical peptides be increased by making them into dimers and macrocycles? KR-12 has previously been determined as the minimalized antimicrobial fragment of the human host defense peptide LL-37. Here, we explore that concept by using KR-12 as the starting point for peptide engineering. Backbone-cyclised KR-12 dimers, tethered by linkers of two to four amino acid residues, were synthesized and their antimicrobial activity, proteolytic stability and structures characterized. A modified KR-12 sequence, with substitutions by previously identified key residues, were also included in the screening panel. The backbone cyclized KR-12 dimers displayed improved antimicrobial activity and increased stability compared to monomeric KR-12. The most active cyclic dimer displayed 16-fold higher antibacterial activity compared to KR-12 against Pseudomonas aeruginosa and Staphylococcus aureus, and 8-fold increased fungicidal activity on Candida albicans. Enhanced antimicrobial activity coincided with increased membrane permeabilization on liposomes, with one distinct discrepancy monomeric KR-12 was much less disruptive on the bacterial lipid composition compared to liposomes composed of fungal lipid extract Circular dichroism showed that the four-linked most active cyclic dimer had 65% helical content when bound to lyso-phosphatidylglycerol micelles, indicating that the helical propensity of the parent peptide is maintained in the new macrocyclic form. In conclusion, the current work on KR-12 suggests that backbone cyclization is an effective strategy for improving both stability and potency of linear antimicrobial peptides.